Phototransparency and water vapor sorption properties of ABA‐type triblock copolymers derived from 6FDA‐TeMPD and poly(2‐methyl‐2‐adamantylmethacrylate). Issue 32 (6th May 2016) - Ando, Shota; Konishi, Shimpei; Yoshida, Akihiro; Nagai, Kazukiyo
ABSTRACT: The phototransparency and water vapor sorption properties of ABA‐type triblock copolymer membranes derived from 4, 4‐(hexafluoroisopropylidene) diphthalic anhydride‐2, 3, 5, 6‐tetramethyl‐1, 4‐phenylenediamine (PI) and poly(2‐methyl‐2‐adamantylmethacrylate) (PMAdMA) were investigated, with focus on the effect of the adamantane component. The phototransparency of PMAdMA‐ block ‐PI‐ block ‐PMAdMA [Block(PI/PMAdMA)] was about 10–20% higher than that of poly(methyl methacrylate)‐ block ‐PI‐ block ‐Poly(methylmethacrylate) [Block(PI/PMMA)] because the high symmetric structure of adamantane inhibited photoabsorbance. The water vapor solubility of Block(PI/PMAdMA) decreased with increased PMAdMA because the PMAdMA had a hydrophobic property. Interestingly, in all relative‐pressure regions, Block(PI/PMAdMA) with the least PMAdMA content showed a higher solubility coefficient than PI because the high mobility of PMAdMA in Block(PI/PMAdMA) resulted in additional sorption sites in the PI segment. A comparison of Block(PI/PMAdMA) with Block(PI/PMMA) in terms of relative pressure at the beginning of clustering further revealed that cluster formation in Block(PI/PMAdMA) was inhibited compared with Block(PI/PMMA) because bulky structure of adamantane restricted the mobility of the polymer main chain. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43795. Abstract :